2005
DOI: 10.1016/j.neuron.2005.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between NMDA Receptor and Acid-Sensing Ion Channel Contributes to Ischemic Neuronal Death

Abstract: Acid-sensing ion channels (ASICs) composed of ASIC1a subunit exhibit a high Ca(2+) permeability and play important roles in synaptic plasticity and acid-induced cell death. Here, we show that ischemia enhances ASIC currents through the phosphorylation at Ser478 and Ser479 of ASIC1a, leading to exacerbated ischemic cell death. The phosphorylation is catalyzed by Ca(2+)/calmodulin-dependent protein kinase II (CaMKII) activity, as a result of activation of NR2B-containing N-methyl-D-aspartate subtype of glutamate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
289
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(302 citation statements)
references
References 49 publications
10
289
2
1
Order By: Relevance
“…The widespread expression of ASIC1a in the brain, its activation by pH drop to the level commonly seen in ischemic brain, and its demonstrated permeability to Ca 2+ strongly suggested that activation of ASIC1a might be involved in the pathology of brain injury. Indeed, a series of recent studies have clearly demonstrated a role for ASIC1a activation in acidosis-mediated and ischemic brain injury [10,12,38,39]. In cultured mouse cortical neurons, activation of ASICs by brief acid incubation induces glutamate receptor-independent Ca 2+ -dependent neuronal injury that is inhibited by specific and non-specific ASIC1a blockade, and by ASIC1 gene knockout [10].…”
Section: Asic1a Activation In Acidosis-mediated and Ischemic Neuronalmentioning
confidence: 99%
“…The widespread expression of ASIC1a in the brain, its activation by pH drop to the level commonly seen in ischemic brain, and its demonstrated permeability to Ca 2+ strongly suggested that activation of ASIC1a might be involved in the pathology of brain injury. Indeed, a series of recent studies have clearly demonstrated a role for ASIC1a activation in acidosis-mediated and ischemic brain injury [10,12,38,39]. In cultured mouse cortical neurons, activation of ASICs by brief acid incubation induces glutamate receptor-independent Ca 2+ -dependent neuronal injury that is inhibited by specific and non-specific ASIC1a blockade, and by ASIC1 gene knockout [10].…”
Section: Asic1a Activation In Acidosis-mediated and Ischemic Neuronalmentioning
confidence: 99%
“…It is generally accepted that ASIC1a forms plasma membrane channels that mediate acidosis-induced neuronal death. 5,6 To determine the specificity of ASIC1a in mediating neuronal death induced by different causes, we compared effects of H 2 O 2 in inducing death of cultured cortical neurons prepared from WT and ASIC1a-knockout mice. 3,23 We found that ASIC1a gene deletion significantly protected neurons against .…”
Section: Resultsmentioning
confidence: 99%
“…1 Homomeric ASIC1a channels are expressed throughout central and peripheral nervous systems and are implicated in learning/memory, pain sensation and neuronal death. [1][2][3][4][5][6][7][8] Among all these functions, mediating ischemic neuronal death was one of the most prominent pathological features of ASIC1a channels. [5][6][7] Although it has been established that severe extracellular acidosis in ischemic brain overactivated ASIC1a and caused neuronal death, 5,6 the death mechanisms remained largely unknown particularly considering that ASIC1a channels completely desensitize within a few seconds during persistent acidosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies highlight a role of ASIC1a in different physiological conditions including synaptic plasticity, learning and memory, transmission of nerve impulses as well as in pathological settings such as ischemia, neuronal injury and epilepsy [8,[13][14][15]. It has been demonstrated that ASICs are required for long-term potentiation (LTP) at cortico-basal lateral amygdala synapses, and are critical for associative fear learning and memory [16].…”
mentioning
confidence: 99%